O nordestino em São Paulo: desconstrução e reconstrução de uma identidade - Borges, Selma Santos (2007)
This dissertation aims at analyzing the identity issue of São Paulo city's migrants from Brazil's northeast, both from point of view of the migrant self image and also how city natives perceive them. It discusses and analyses some of the prejudiced stereotypes through which northeastern migrants are portrayed in São Paulo in their own perception. It tries to pinpoint the manner these discriminations come about, by what means they are felt by the northeastern migrant population and to what extent this affects the concept they have from their homeland. It debates with the current academic production, the exposition of some cultural resistance points, their relationship nets , their customs, attitudes and behaviors brought from their land of origin. The definition of identity and prejudice are key reference onto this research, within a socio-historic approach, in actual fact found on the assessment of 30 closed interviews and one open-ended, with attention to dualities expressed by migrants: deconstruction/ reconstruction, domination/ subjection, discrimination/ resistance. It contemplates from early 1980's, when city's unemployment rates soar, until present days. From this study, it can be noticed that the migrant, when feeling stigmatized, reaches among peers for support to stay in the city